1982
DOI: 10.1007/bf00403722
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of individual variations in sunburn sensitivity in 303 volunteers without photodermatosis

Abstract: Variations in individual sunburn sensitivity have been studied using erythema as the photobiologic criterion. The minimal erythema dose (MED), the minimal dose necessary to elicit an intense erythema (MED++), and an edema (MOD), were determined by Saidman's method. The irradiation was performed with a 2,500-W xenon arc solar simulator fitted with a water filter and WG 305 Schott filter. The high correlation between MED, MED++, and MOD and the existence of saturation phenomenon confirm that determination of MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…MED was proposed as another estimation of skin sensitivity to UV radiation. The two parameters were found to be correlated as shown in a French population (Amblard et al, 1982). Gambichler et al (2006) have also determined the relationship between skin phototypes and MED values for broadband UVB and found significant different mean UVB-MED values between the skin phototype classes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…MED was proposed as another estimation of skin sensitivity to UV radiation. The two parameters were found to be correlated as shown in a French population (Amblard et al, 1982). Gambichler et al (2006) have also determined the relationship between skin phototypes and MED values for broadband UVB and found significant different mean UVB-MED values between the skin phototype classes.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, a significant 1.6 larger value was obtained for phototypes IV than II, in agreement with published data. For instance in a wide study of the variation in sunburn sensitivity, Amblard et al (1982) found a ratio of 1.8 between the UVB-MED for photoypes IV and II. Other authors reported values of 1.4 (McGregor et al, 2002;Gambichler et al, 2006) and 1.5 (Westerhof et al, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…Several authors have investigated the relationship between Fitzpatrick skin type and MED (Amblard et al., ; Baron et al., ; Harrison and Young, ; Hemminki et al., ; Sayre et al., ; Stern and Momtaz, ; Westerhof et al., ; Wulf et al., ; Youn et al., ). In general, these studies have shown increased MED with skin type, but with considerable intergroup variation.…”
Section: Experimentally Quantifying the Photobiological Effects Of Pimentioning
confidence: 99%
“…For example, a study found that only 2/3 people self-identified as the same skin type after repeat questioning a few months later (Ravnbak, 2010). Several authors have investigated the relationship between Fitzpatrick skin type and MED (Amblard et al, 1982;Baron et al, 1999;Harrison and Young, 2002;Hemminki et al, 2002;Sayre et al, 1981;Stern and Momtaz, 1984;Westerhof et al, 1990;Wulf et al, 2010;Youn et al, 1997). In general, these studies have shown increased MED with skin type, but with considerable intergroup variation.…”
Section: Relationship Between Med and Fitzpatrick Skin Typementioning
confidence: 99%
“…54 That melanin provides effective photoprotection is suggested by the fact that poorly melanized skin is far more vulnerable than melanized skin to acute and chronic injury caused by ultraviolet radiation (sunburn and photoaging or photocarcinogenesis, respectively). [55][56][57] The role of melanin is perhaps more definitively indicated by the fact that the degree of sensitivity to ultraviolet radiation differs between pigmented and depigmented areas of the same person -for example, the normal skin and the diseased skin of patients with vitiligo 58 (Fig. 2).…”
Section: The Photoprotective Role Of Melanocytesmentioning
confidence: 99%